Navigating Educational Challenges in Pakistan: Unraveling Issues and Proposing Remedies - Zohaib Hassan Sain; Rene. M. Babiera II (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study investigates challenges within Pakistan's education system and proposes solutions, exploring changes since independence and their impacts. Education's gradual yet impactful influence on the social, political, and cultural landscape is acknowledged, emphasizing its role in organizational problem-solving, design, and globalized, quality-based systems. The article scrutinizes the current state of education in Pakistan, utilizing a mix of qualitative and quantitative approaches with a reliance on secondary data. The discussion focuses on configuration, access, excellence, future projections, and persistent issues in Pakistan's education system. Balancing quality and quantity are crucial, ensuring education cultivates individuals capable of ethically contributing to societal development objectives. The study emphasizes using education as a catalyst to actively engage the brightest youth in the country's development. Recommendations include implementing projects to raise awareness about the benefits of the educational system, elevating standards, encouraging participation in organizations creating educational opportunities, and adapting education to contemporary circumstances. Fostering stakeholder interaction is proposed to identify problems and explore potential solutions